Quadrature spatial media-based modulation with RF mirrors - Pillay, Narushan; Xu, HongJun (IET communications, 2017)
The use of radio frequency (RF) mirrors to improve spectral efficiency is a recently introduced technique. The authors investigate its application to single RF chain and inter-channel interference-free communications. The technique is first applied to improve the error performance of a conventional single-input multiple-output (SIMO) scheme, in the form of SIMO media-based modulation (SIMO-MBM) with single-mirror activation pattern (MAP). Significant improvement in error performance is demonstrated. The theoretical average bit error probability (ABEP) of SIMO-MBM with single MAP is formulated and serves to validate the Monte-Carlo simulation results. The application of RF mirrors to further improve spectral efficiency in quadrature spatial modulation is then proposed, in the form of quadrature spatial media-based modulation (QSMBM) and is able to achieve very large spectral efficiencies, while maintaining relatively good error performance. The theoretical ABEP of QSMBM is formulated and shown to agree well with Monte-Carlo simulation results. Finally, MAP selection for QSMBM is investigated. Due to the high computational complexity and memory requirements of optimal MAP selection, low-complexity suboptimal algorithms for MAP selection are investigated. A significant improvement in the error performance of QSMBM is demonstrated with these algorithms.